PENGARUH MINAT BELAJAR TERHADAP MOTIVASI BELAJAR SISWA DI SMA NEGERI 1 WAYTENONG - Miftah Shofiyah Novianti; Nurdin Nurdin; Pujiati Pujiati; Yon Rizal (Journal of Social Science Education, 2022)
Abscract - This study aims to determine the effect of interest in learning to the learning motivation of students at SMA Negeri 1 Waytenong. The method used in this research is descriptive verification with a quantitative approach. The results of this study are that there is a positive and significant influence of interest in learning and motivation to learn, which is indicated by the value of tcount> ttable, namely 7.124> 1.661 with a significance level of 0.000.